Managing complexity in the supply chain - Braithwaite, Alan (Henry Stewart Talks, 2010)
The concept of complexity, Complexity applied to business and supply chains, The dimensions of supply chain complexity, Measuring complexity: tools and techniques, Cost-to-Serve(R): the complexity solver, Actions to manage and master complexity, The bottom line benefits for business